Laparoscopic surgical access in morbidly obese women undergoing endometrial cancer surgery: Repurposing the left upper quadrant approach. (January 2020) - Varghese, Aaron; Peijnenburg, Elizabeth; Stone, Rebecca L.; Wethington, Stephanie L.; Levinson, Kimberly L.; Beavis, Anna; Yen, Ting-Tai; Tanner, Edward J.; Fader, Amanda N.
Abstract: Objective: The study purpose was to report the outcomes of patients undergoing endometrial cancer surgical staging with laparoscopic abdominal access entry using a left upper quadrant (LUQ) access technique. Methods: This was a retrospective cohort study conducted from 1 January 2013 to 1 January 2018. The setting was an academic, single institution gynecologic oncology service with a high volume of minimally invasive surgery (MIS). The patient cohort included obese (defined as BMI > 30 kg/m 2 ) or morbidly obese (BMI > 40 kg/m 2 ) women undergoing MIS for endometrial cancer staging. All patients underwent laparoscopic abdominal access via a 5-mm or 10-mm optical trocar system using a LUQ technique. Results: In total, 317 patients were included with a median age of 54 years (range, 24–79) and median BMI 42.5 kg/m 2 (range, 32–70); 60 % morbidly obese. Successful LUQ access was achieved in 98.1 %. Of those with a failed LUQ approach, two had undergone previous LUQ surgery and 4 had ≥1 previous midline vertical incisions. There was one LUQ trocar-related visceral injury (0.3 %) and no vascular injuries during the study period. Conclusion: A LUQ abdominal technique is a safe and reliable method of laparoscopic access in morbidly obese women undergoing MIS for endometrial cancer staging. This may be the preferred method of laparoscopic access for women with a panniculus or central adiposity, given the caudal displacement of the umbilicus and poor correlation with intraperitoneal anatomic landmarks in this setting.